Asymptomatic Clostridium difficile colonization in two Australian tertiary hospitals, 2012–2014: prospective, repeated cross-sectional study. (January 2017) - Furuya-Kanamori, L.; Clements, A.C.A.; Foster, N.F.; Huber, C.A.; Hong, S.; Harris-Brown, T.; Yakob, L.; Paterson, D.L.; Riley, T.V.
Abstract: Objectives: To investigate the prevalence and risk factors for asymptomatic toxigenic (TCD) and nontoxigenic Clostridium difficile (NTCD) colonization in a broad cross section of the general hospital population over a 3-year period. Methods: Patients without diarrhoea admitted to two Australian tertiary hospitals were randomly selected through six repeated cross-sectional surveys conducted between 2012 and 2014. Stool specimens were cultured under anaerobic conditions, and C. difficile isolates were tested for the presence of toxin genes and ribotyped. Patients were then grouped into noncolonized, TCD colonized or NTCD colonized for identifying risk factors using multinomial logistic regression models. Results: A total of 1380 asymptomatic patients were enrolled; 76 patients (5.5%) were TCD colonized and 28 (2.0%) were NTCD colonized. There was a decreasing annual trend in TCD colonization, and asymptomatic colonization was more prevalent during the summer than winter months. TCD colonization was associated with gastro-oesophageal reflux disease (relative risk ratio (RRR) = 2.20; 95% confidence interval (CI) 1.17–4.14), higher number of admissions in the previous year (RRR = 1.24; 95% CI 1.10–1.39) and antimicrobial exposure during the current admission (RRR = 2.78; 95% CI 1.23–6.28). NTCD colonization was associated with chronic obstructive pulmonary disease (RRR = 3.88; 95% CI 1.66–9.07) and chronic kidney failure (RRR = 5.78; 95% CI 2.29–14.59). Forty-eight different ribotypes were identified, with 014/020 ( n = 23), 018 ( n = 10) and 056 ( n = 6) being the most commonly isolated. Conclusions: Risk factors differ between patients with asymptomatic colonization by toxigenic and nontoxigenic strains. Given that morbidity is largely driven by toxigenic strains, this novel finding has important implications for disease control and prevention.